In vitro growth and cell wall degrading enzyme production by Argentinean isolates of Macrophomina phaseolina, the causative agent of charcoal rot in corn - Ramos, Araceli Marcela (2016)
Macrophomina phaseolina is a polyphagous phytopathogen, causing stalk rot on many commercially important species. Damages caused by this pathogen in soybean and maize crops in Argentina during drought and hot weather have increased due its ability to survive as sclerotia in soil and crop debris under non-till practices. In this work, we explored the in vitro production of plant cell wall-degrading enzymes [pectinases (polygalacturonase and polymethylgalacturonase); cellulases (endoglucanase); hemicellulases (endoxylanase) and the ligninolytic enzyme laccase] by several Argentinean isolates of M. phaseolina, and assessed the pathogenicity of these isolates as a preliminary step to establish the role of these enzymes in M. phaseolina–maize interaction. The isolates were grown in liquid synthetic medium supplemented with glucose, pectin, carboxymethylcellulose or xylan as carbon sources and/or enzyme inducers and glutamic acid as nitrogen source. Pectinases were the first cell wall-degrading enzymes detected and the activities obtained (polygalacturonase activity was between 0.4 and 1.3 U/ml and polymethylgalacturonase between 0.15 and 1.3 U/ml) were higher than those of cellulases and xylanases, which appeared later and in a lesser magnitude. This sequence would promote initial tissue maceration followed by cell wall degradation. Laccase was detected in all the isolates evaluated (activity was between 36 U/l and 63 U/l). The aggressiveness of the isolates was tested in maize, sunflower and watermelon seeds, being high on all the plants assayed. This study reports for the first time the potential of different isolates of M. phaseolina to produce plant cell wall-degrading enzymes in submerged fermentation.